The effects of daily physical activity on functional fitness, isokinetic strength and body composition in elderly community-dwelling women - Monteiro, A.M. (2019)
Physical inactivity has been classified as a public health problem. The excess fat with muscle loss along with the general decline of physical and functional capacity. The aim of this study was to evaluate the relative contribution of objectively estimated daily physical activity (PA) in functional fitness, isokinetic strength and body composition in community-dwelling elderly women. Sixty elderly female volunteered for this research, with 67.69 ± 5.30 years old. Daily PA was assessed using accelerometers for 7 days. The evaluation and quantification of body composition, total lean body mass, fat mass, total body fat mass and bone mineral density, were made with the DXA equipment. Body Mass Index (BMI) was also calculated. The functional fitness (FF) assessment was performed using Functional Fitness Test. The knee extensor and flexor isokinetic strength was evaluated in both lower limbs, using a dynamometer at two different angular velocities: 60°/sec. and 180°/sec. Body Composition, Bone Mineral Density (p = 0.014) and Fat Mass (p = 0.029) were statistically lowers in the 3rd tertile compared to the 2nd one. The knee flexion peak torque at 180°/sec on the dominant leg (p = 0.051) and non-dominant leg (p = 0.020) was statistically different between the less active group and the most active group. For the FF, no significant differences between groups were found. Our results suggest that daily PA seems to induce benefits on BMI and % Fat Mass as well as on isokinetic knee flexion strength of independent and community dwelling-resident’s older women.